Thermal stability of arsenic complexes in soils - Dousova, Barbora; Buzek, Frantisek; Cejkova, Bohuslava; Jackova, Iva; Lnenickova, Zdena (Journal of hazardous materials, 2021)
The release of soil arsenic (As) in an unsaturated zone under oxidative conditions and at two temperatures simulating the seasonal effect (15 °C and 23 °C) was studied in four cultivated soils from the Elbe River catchment (Czech Republic, Central Europe). The soils with a low geogenic As background contained from 10 to 50 µg.g-1 of As, mostly originating from atmospheric deposition in the past. The temperature effect on the stability of As in soils was studied in connection with the stability of hydrated iron (Fe) oxides and dissolved organic carbon (DOC), as essential binding partners of As in soils. The temperature impact on As release was related to the actual As binding in soil determined by the sequential leaching. With predominant As binding to amorphous and poorly crystalline Fe phases the higher temperature (23 °C) increased As release up to twice compare to 15 °C. In the soils with a low total Fe and the preferential As binding to well-crystallised Fe phases the temperature effect on As release was negligible. Unlike Fe, the release of DOC is strongly temperature dependent, therefore As mobilisation was controlled by the DOC concentration. A higher experimental temperature (23 °C) supported the formation of DOC and the consequent release of As and Fe into the soil solution.
Keywords: Soil Pollutants; Iron; Unsaturated zone; látky znečišťující půdu; železo; arsen; Soil; Temperature; Arsenic; Czech Republic; půda; Mobilisation; Česká republika